The Teachers’ Demotivation Causes and Strategies in Teaching English Online during Covid-19 Pandemic - Evi Sastra Sibran; Alamsyah Harahap; Wisma Yunita (English Education Study Program Faculty of Teacher Training and Education, 2023)
The objective of this research was to investigate the causes of teachers’ demotivation and to reveal the strategies used by the teachers to resolve demotivation in teaching English online during Covid-19 pandemic in Bengkulu. This research employed mix method design which involved both collecting and analyzing quantitative and qualitative data. The instrument used in this research were questionnaire and interview. The questionnaires and interviews were distributed to the junior high school English teachers in Bengkulu. The results showed that English teachers in Bengkulu had demotivation during online learning. Teaching profession, curriculum, working conditions, students and parents, colleagues and school administrator, and physical conditions were the causes of the teachers’ demotivation. In addition, it is found that there was the only one strategy by the teachers which was self-control. The teachers rarely used Professional development and instructional strategies as strategy during online learning pandemic Covid-19. Finally, it is suggested to the students to understand that their behavior in classroom has a significant impact toward teachers’ demotivation, so the teachers are motivated in teaching. It is also suggested to next researcher to conduct similar research in larger scope about teachers’ demotivation, and the correlation between teachers’ demotivation and teachers’ performance.